HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN SERVIS ATAS DALAM PERMAINAN BOLA VOLI - Pahrian, Agus; NL Esser, Balkis Ratu (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
Volleyball games include learning materials in SMP / MTS education curriculum. The service technique is one of the important factors in volleyball that serves to hit the first start of the game and the initial attack for a team. The result of volleyball service can be affected by arm muscle strength. Based on background problems researchers can formulate a problem that will be the focus of this research. The problem is formulated in a question which reads as follows: "Is there a Relation of Arm Muscle Strength to Top Service Accuracy in Volley Ball Games to Students Following Extracurricular Volleyball At MTS Nurul Huda Nyerot Village Jonggat Sub-district, Central Lombok Regency Year 2015?". this research is to know the Relationship of Arm Muscle Strength on Top Service Accuracy In Volley Ball Games On Students Following Extracurricular Ball Volley In MTS Nurul Huda Nyerot Village Jonggat Subdistrict Central Lombok Regency Year 2015. The number of samples used is amounted to 14 people. Data collection techniques used are (1) observation method, (2) method of documentation, (3) action test method. Based on the results of data analysis using product moment correlation analysis obtained r 0.556 at 5% significant level then r table value is 0,532, mean value of r count is bigger than r table value (0,556> 0,532). With Thus Results Research Shows That There is Significant Correlation Between Arm Strength Against Top Service Accomplishment On Students Following Extracurricular Volleyball At Mts Nurul Huda Nyerot Village Jonggat Sub-district Central Lombok Regency Year 2015